Evaluation of an Obstetric Medicines Information Service: Analysis of Medicines Enquiries and User Satisfaction - Mukadam, Nabeelah (Curtin University, 2022)
Medicines information services in pregnancy and breastfeeding ensure safe use of medicines in the mother, with minimal harm to the fetus or child. This study analysed 20 years of enquiries to an information service in Perth, revealing trends in the number and sources of enquiries and medications of concern over the years. A subsequent user satisfaction survey indicated user need and value of the service. This analysis will inform continuous quality improvement and resourcing recommendations.